Hubungan Komunikasi Terapeutik Perawat dengan Kepuasan Layanan Pasien di RS X Kota Palembang Tahun 2022 - Ria Wulandari; Rini Herdiani; Ranida Arsi; Selamat Parmin (Penerbit Yayasan Daarul Huda Kruengmane, 2022)
A nurse needs to have better therapeutic communication skills in carrying out her role so that she can determine the success of professional nursing services or care by paying attention to the holistic needs of patients. The purpose of this study was to determine the relationship between nurse therapeutic communication and patient satisfaction at X Hospital Palembang City in 2022. This type of research is analytic survey with a cross sectional approach. The study was conducted with a sample of 100 inpatients. Data processing: Editing, Coding, Entry Cleaning. Univariate and bivariate data analysis. The results showed that there was a relationship between nurse therapeutic communication and patient service satisfaction (p value. 0.020). Suggestions for maintaining therapeutic communication for human resource development are further enhanced by holding outreach, training, seminars and workshops regarding the implementation of therapeutic communication.